Challenging Analytic Data Opportunities in Smart Health with Algorithm (Study Case: Bumi Medika Ganesha ITB) - Hadikusuma, Aristyo; Asmoro, Anung; Rurianto, Joko (School of Computing, Telkom University, 2023)
Weka is a tool to help the data science to clustering data. Weka has feature K-means which help clustering data to spesific analysis. Clustering analysis is a technique for categorizing and dividing objects into groups. Each object has certain characteristics. Because the data has a lot of variety and quantity,By using this K-Means algorithm the patient temperature data already obtained will be grouped into several clusters. Grouping of data by clustering is expected to be a strategy for decision making.